MECHANISMS FOR THE FORMATION OF HEALTHY THINKING IN STUDENTS OF HIGHER EDUCATIONAL INSTITUTIONS (Innovative Technologica: Methodical Research Journal, 2023)
In recent years, the role of a person in all spheres of life has been changing, the importance of complex intellectual work is increasing, and the possibilities of creative application of forces are expanding. In this context, the problems associated with ensuring a high level of health of modern and future generations of people, their adaptation to rapidly changing conditions of the social and natural environment are inevitably becoming more acute. Therefore, in order to meet modern requirements and be ready for changes in living conditions (both spiritual and industrial), it is not enough to have only a high level of education and culture, deep professional knowledge and skills - it is necessary to have good health.